RASISME VERBAL DAN RELASI KUASA PADA FILM PENGEPUNGAN DI BUKIT DURI - Selli Andalia Ananda; Muhammad Hasan Basori (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2026)
Racism against the Chinese ethnic group remains a social issue that continues to be represented across various forms of media, including film. Pengepungan di Bukit Duri, directed by Joko Anwar, portrays various forms of discrimination against the Chinese ethnic community that reflect social realities in Indonesia. This study aims to analyze the representation of racism against the Chinese ethnic group in the film using John Fiske’s semiotic approach. This research employs a descriptive qualitative method, with data collected from scenes, dialogues, and visual elements that contain representations of racism. The analysis was conducted through John Fiske’s three levels of codes: reality, representation, and ideology. The findings reveal that racism is represented through verbal racism and power relations directed toward the Chinese ethnic group. At the reality level, racism is depicted through discriminatory remarks, identity labeling, and prejudices that emerge in interactions between characters. At the representation level, the use of camera techniques, lighting, and sound design reinforces the discriminatory meanings constructed within the film’s narrative. At the ideological level, the film positions the Chinese ethnic group as a minority community that experiences unequal power relations and social marginalization. The findings indicate that film functions as a medium of representation that both reflects and critiques racist practices against the Chinese ethnic group within Indonesian society.